Paleo- to Mesoproterozoic supercontinent cycle – emphasizing Fennoscandia - Luoto, Toni (Helsingin yliopisto, 2025)
Throughout Earth's history, continents have periodically formed supercontinents and then fragmented into separate continental blocks in events known as supercontinent cycles. These cycles significantly influence climate, life, and geological processes. It has also been established that there is a positive feedback loop between mantle convection and the supercontinent cycle: while mantle convection drives the assembly and breakup of supercontinents, supercontinents, in turn, influence the mantle convection patterns. This interconnectedness highlights the complex relationship between tectonics, mineral resources, and Earth's dynamic systems. This dissertation examines the evolution of the Fennoscandian Shield during the Paleo-Mesoproterozoic Nuna supercontinent cycle, employing paleomagnetism as the primary method. Paleomagnetic studies were conducted on ca. 1330 Ma dykes in Bornholm, Baltic Sea, and on mafic intrusions formed during the 1920–1770 Ma Svecofennian orogeny in Finland. These studies span the time from the assembly to the breakup of the Nuna supercontinent. In addition to new paleomagnetic data, this research utilizes existing high-quality paleomagnetic records compiled in the Nordic Paleomagnetic Workshops in 2017 and 2022. Global high-quality paleomagnetic data indicate significant oscillations in paleomagnetic pole positions of several cratons at ca. 2060–1860 Ma, during the early stages of the Nuna supercontinent amalgamation, followed by a prolonged period of relatively minor plate motions. Possible explanations for these oscillations include erroneous paleomagnetic data, a geomagnetic field deviating from the geocentric axial dipole field, rapid movement of lithospheric plates, or true polar wander (TPW), in which Earth's entire solid outer shell moves relative to the Earth's rotational axis. However, the quality of paleomagnetic data and models suggests that TPW is the most likely explanation for these oscillations. These observations align with a previously proposed theory, based on empirical ...